Application of biofilm-chitin oral vaccine on streptococcosis infected red hybrid tilapia (Oreochromis sp.) - Kahieshesfandiari, Mahdi (2018)
Malaysia has started developing tilapia culture and has become one of the top countries in Asia. However, disease such as streptococcosis is one of the obstacles in the aquaculture industry. Two main and renowned species are Streptococcus agalactiae and Streptococcus iniae. For prevention of streptococcosis, the use of antibiotics is discouraged. Therefore, developing vaccines to prevent streptococcosis is highly recommended. In this study, a feed-based oral biofilm-chitin vaccine was developed and tested in red hybrid tilapia to prevent streptococcosis. For identification, the results confirmed ten isolates of S. agalactiae and three isolates of S. iniae by API20 strep and 16SrRNA gene sequencing. This was the first report on the isolation of S. iniae from red hybrid tilapia in Malaysia.